Self-Balancing Exoskeleton Robots Designed to Facilitate Multiple Rehabilitation Training Movements - Dingkui Tian; Wentao Li; Jinke Li; Feng Li; Ziqiang Chen; Yong He; Jianquan Sun; Xinyu Wu (IEEE, 2024)
This study presents the biomimetic design of the structure and controller of AutoLEE-II, a self-balancing exoskeleton developed to assist patients in performing multiple rehabilitation movements without crutches or other supporting equipment. Its structural design is founded upon the human body structure, with an eliminated axis deviation and a raised CoM of the exoskeleton. The controller is a physical parameter-independent controller based on the CoM modification. Thus, the exoskeleton can adapt to patients with different physical parameters. Five subjects underwent exoskeleton-assisted rehabilitation training experiments, including squatting, tilting, and walking trainings. The results showed that the exoskeleton can assist patients in completing various rehabilitation exercises and help them maintain their balance during the rehabilitation training. This helpful role of the exoskeleton in rehabilitation training is analyzed through an electromyography (EMG) data analysis. The findings revealed that wearing the exoskeleton can reduce the activity of the lower limb muscles by approximately 20–30% when performing the same rehabilitation exercises.